Preconditioning intensive training ameliorates reduction of transcription biofactors of PGC1?-pathway in paretic muscle due to cerebral ischemia - Abbasian, Sadegh; Ravasi, Ali Asghar; Haghighi, Amir Hossein; Aydin, Suna; Delbari, Ahmad; Aydin, Suleyman (Taylor & Francis Ltd, 2023)
Exercise training increases fibronectin type III domain-containing protein 5 (FNDC5/irisin) via the peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1 alpha)-pathway. The PGC1 alpha pathway induced FNDCs/irisin changes in response to exercise training and ischemic stroke are not entirely understood. We investigated the relation of the PGC-1 alpha/FNDCs/irisin pathway to exercise training and to the pathophysiology of ischemic stroke in paretic muscles of stroke-induced rat models. We induced cerebral ischemia following completion of high-intensity interval training (HIIT) to evaluate PGC1 alpha-pathway biofactors in paretic muscles. To define the underlying molecular mechanisms for improvement in paretic muscles following cerebral ischemia, we evaluated PCG-1 alpha-pathway factors using immunofluorescence tracking and enzyme-linked immunosorbent assay (ELISA) immunoassay. We found that HIIT for 3 weeks produced increased expression and release of PGC-1 alpha-pathway biomarkers in both the serum and paretic muscle of stroke-induced rats. We also found a close relation between the expression of PCG-lapathway factors in skeletal muscle and their concentration in blood. We found that PGC-1 alpha-pathway biomarkers cause irisin up-regulation following induction of cerebral ischemia. The reduction in neurofunctional deficits following increased PGC-1 alpha-pathway biomarkers suggests that these factors may act as markers of improvement in paretic muscle healing following cerebral ischemia.
Keywords: Biofactors; cerebral ischemia; exercise; irisin; muscle wasting; paretic muscle; PGC1 alpha pathway; rats; stroke; training